Improving the performance of retail stores subject to execution errors: coordination versus RFID technology - Rekik, Yacine; Jemai, Zied; Sahin, Evren; Dallery, Yves (OR Spectrum, 2007)
This paper analyzes a Newsvendor type inventory model in which a manufacturer sells a single product to a retailer store whose inventory is subject to errors stemming from execution problems. Hence, within the store, all of the products are not available on shelf for sales either because the replenishment of the shelf from the backroom is subject to execution errors that mainly result in products lost in the backroom or products misplaced on the other shelves of the store. Two situations are compared: in the first situation, the two supply chain actors are aware of errors and optimize their ordering decisions by taking into account this issue. The second situation deals with the case where an advanced automatic identification system such as the Radio Frequency Identification technology is deployed in order to eliminate errors. Each situation is developed for three scenarios: in the centralized scenario, the authors consider a single decision-maker who is concerned with maximizing the entire supply chain's profit; in the decentralized uncoordinated scenario, the retailer and the manufacturer act as different parties and do not cooperate.